2013
DOI: 10.1142/s0192415x13500365
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of NMDA Receptors byWithania somniferaon Hippocampal CA1 Pyramidal Neurons

Abstract: In Ayurveda,Withania somnifera (WS) is used as a medicine to maintain mental and physical health as well as to enhance memory. In this study, the methanolic extract of WS(mWS) was tested for its electrical influence on hippocampal CA1 pyramidal neurons using a patch clamp technique. In current clamp mode under a high chloride pipette solution, mWS (400 ng/μl) induced remarkable membrane depolarization (9.75 ± 2.54 mV, n = 6) of CA1 neurons. The mWS-induced depolarization was dose-dependent, reproducible, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In addition, the inward currents induced by SS were partially blocked by picrotoxin, a broad GABA A receptor antagonist, suggesting that SS exhibits GABA-mimetic activity via synaptic and extrasynaptic GABA A receptors ( Figure 8 G,H). This provides evidence that SS acts directly on the GABA binding site of CA1 pyramidal neurons in the hippocampus [ 17 ]. These results are in agreement with a previous study [ 38 ], which reported that Withania somnifera acts at a GABA receptor by inhibiting GABA A receptor agonists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the inward currents induced by SS were partially blocked by picrotoxin, a broad GABA A receptor antagonist, suggesting that SS exhibits GABA-mimetic activity via synaptic and extrasynaptic GABA A receptors ( Figure 8 G,H). This provides evidence that SS acts directly on the GABA binding site of CA1 pyramidal neurons in the hippocampus [ 17 ]. These results are in agreement with a previous study [ 38 ], which reported that Withania somnifera acts at a GABA receptor by inhibiting GABA A receptor agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Brain slices were prepared as described by [ 17 ] earlier study with slight modifications in position of brain used. Immature ICR male mice (5–20 Postnatal days) were sacrificed by cervical dislocation between 10:00 and 12:00 h and their brains rapidly removed and placed in the ice-cold low calcium (0.5 mM), high magnesium (6 mM) bicarbonate-buffered artificial cerebrospinal fluid (ACSF) (pH 7.4 when bubbled with 95% O 2 and 5% CO 2 )).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A plasma and CSF level of GABA is higher after initial withdrawal than after longer periods of abstinence. [ 47 ] Diazepam, an established GABA A agonist and anti-addictive compound, also showed increase in corticohippocampal GABA levels. Similar to previous reports, we also found an increase in serotonin levels in the corticohippocampal lysates of ethanol-exposed animals[ 44 48 ] suggesting either excess release or reduced uptake of serotonin.…”
Section: Discussionmentioning
confidence: 99%